Porcine and Rangiferine Brucellosis: Brucella suis - Iowa State University Center for Food Security and Public Health (Iowa State University Digital Repository, 2009)
Porcine brucellosis, caused by the bacterium Brucella suis, is an economically important cause of reproductive losses in pigs. This organism can be maintained in wild and feral swine, complicating eradication efforts in domesticated pigs. One variant, found only in Europe, is also maintained in hares. Some variants of B. suis mainly affect caribou, reindeer or rodents, and are not important in pigs. B. suis is zoonotic. In humans, brucellosis can be a serious, debilitating and sometimes chronic disease that may affect a variety of organs. Most cases are the result of occupational exposure to infected animals. B. suis has also been weaponized and could be used in a bioterrorist attack.